Photopolymerization of acrylamide with benzophenone/methylated-β-cyclodextrin inclusion complex in the presence of jeffamine based dendrimers as coinitiators in aqueous media - Temel, Gokhan; Parali, Tezcan; Tulu, Metin; Arsu, Nergis (ELSEVIER SCIENCE SA, 2010)
BP/Me-beta-CD inclusion complex was synthesized and used in photoinduced free radical polymerization of acrylamide as a type II photoinitiator in the presence of a dendritic co-initiator. Characterization and photophysical studies of the inclusion complex were determined by H-1 NMR, UV, laser flash photolysis and phosphorescence spectroscopy. According to acrylamide polymerization of the BP/Me-beta-CD water soluble photoinitiator, BP/Me-beta-CD initiates polymerization of acrylamide effectively with six and twelve armed dendritic co-initiators in aqueous media. The 24 armed dendritic co-initiator was not as efficient as the six and twelve armed dendritic co-initiators with the BP/Me-beta-CD inclusion complex, due to the sterical hindrance of the amine groups in the co-initiator. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Benzophenone; Water soluble photoinitiator; Cyclodextrin; Dendrimer; Free radical polymerization; POLY(PROPYLENE IMINE) DENDRIMERS; FREE-RADICAL POLYMERIZATION; HOST/GUEST COMPLEX; PHOTOCHEMISTRY; WATER; Chemistry